2017
DOI: 10.1088/0256-307x/34/7/075202
|View full text |Cite
|
Sign up to set email alerts
|

Forming of Space Charge Wave with Broad Frequency Spectrum in Helical Relativistic Two-Stream Electron Beams

Abstract: We elaborate a quadratic nonlinear theory of plural interactions of growing space charge wave (SCW) harmonics during the development of the two-stream instability in helical relativistic electron beams. It is found that in helical two-stream electron beams the growth rate of the two-stream instability increases with the beam entrance angle. An SCW with the broad frequency spectrum, in which higher harmonics have higher amplitudes, forms when the frequency of the first SCW harmonic is much less than the critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
0
14
0
5
Order By: Relevance
“…Since the amplitude of the evanescent wave decreases rapidly, we do not take this wave into further account. It is also worth noting that equation (14) allows two real solutions corresponding to slow and fast waves [1,13,15] besides two complex solutions while cr   …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the amplitude of the evanescent wave decreases rapidly, we do not take this wave into further account. It is also worth noting that equation (14) allows two real solutions corresponding to slow and fast waves [1,13,15] besides two complex solutions while cr   …”
Section: Discussionmentioning
confidence: 99%
“…Further search of the multiharmonic operation modes has revealed that excitation of multiharmonic SCWs happens more effectively in helical two-stream relativistic electron beams [13]. In the framework of the small-signal approximation it was found out that in helical two-velocity relativistic electron beams the growth rates of the two-stream instability are higher than in the straight beams.…”
Section: -2mentioning
confidence: 99%
See 3 more Smart Citations